Profile and environmental perception of visitors at river dolphins floating, Anavilhanas National Park, Novo Airão – AM - Marcelo Derzi Vidal (Revista Brasileira de Pesquisa em Turismo, 2013)
In River Dolphins Floating, situated in the Anavilhanas National Park, municipality of Novo Airão-AM, develops tourism interactive with Amazon River Dolphin (Inia geoffrensis). Interactions with those animals began in 1998 and since then, the enterprise has become the main tourist spot in the city. Here is presented the profile and perception of environmental 119 visitors of the River Dolphins Floating and concluded that tourism interactive with cetaceans in Anavilhanas National Park is positive both in the economic and social council of the Novo Airão, therefore directly and indirectly promotes the generation income, as under environmental, since the tourism model implemented is seen by visitors as a tool that contributes to the conservation of Amazon River Dolphin.